Performance evaluation of uncoated carbide tool in high speed drilling of Ti6Al4V - Abd. Rahim, Erween; Kamdani, Kamaruddin; Sharif, Safian (The Japan Society of Mechanical Engineer, 2008)

(untitled)
This paper presents the experimental investigation into the performance of the uncoated carbide tool when high speed drilling (HSD) of Ti6Al4V. Machining responses such as thrust force, torque, vibration, chip formation and surface integrity of drilled surface were evaluated at various cutting conditions. Results show that cutting speed and feed significantly influenced the above responses. Folded wavy type chips and curly type chips were produced under all tested cutting conditions. It was also found that the transition from aperiodic to periodic chip formation occurred as the cutting speed increases. In addition, improvement of the drilling performance was also recorded as a result of reduction of acceleration amplitude during peck drilling method was adopted. Observation on the subsurface of the drilled workpiece indicates a severe plastic deformation at all tested cutting conditions.